2016
DOI: 10.1016/j.bcp.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 inhibits vascular smooth muscle cell dedifferentiation through mitochondrial dynamics regulation

Abstract: Glucagon-like peptide-1 (GLP-1) is a neuroendocrine hormone produced by gastrointestinal tract in response to food ingestion. GLP-1 plays a very important role in the glucose homeostasis by stimulating glucose-dependent insulin secretion, inhibiting glucagon secretion, inhibiting gastric emptying, reducing appetite and food intake. Because of these actions, the GLP-1 peptide-mimetic exenatide is one of the most promising new medicine for the treatment of type 2 diabetes. In vivo treatments with GLP-1 or exenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Cells were transferred into an incubation chamber (37°C, 5% CO 2 ), and images were acquired using LSM-800 time-lapse confocal microscopy with ×40 oil immersion objective lens. Z-stacks of thresholder images were volume reconstituted using the VolumeJ plug-in (31). We can track changes in mitochondrial size that ranged from 0.039 to 0.873 μm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were transferred into an incubation chamber (37°C, 5% CO 2 ), and images were acquired using LSM-800 time-lapse confocal microscopy with ×40 oil immersion objective lens. Z-stacks of thresholder images were volume reconstituted using the VolumeJ plug-in (31). We can track changes in mitochondrial size that ranged from 0.039 to 0.873 μm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The A7r5 cell line is widely used in vitro to study the physiology and pathophysiology of VSMCs [ 13 , 14 ]. Some studies demonstrated this cell line as the “contractile” phenotype [ 17 , 18 ], while others showed the A7r5 cell line is “synthetic” phenotype VSMCs [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The A7r5 cell line has been widely used in vitro to study the physiology and pathophysiology of VSMCs [ 13 , 14 ]. However, it has lost some VSMCs selectivity and has many differences from primary cultured VSMCs.…”
Section: Methodsmentioning
confidence: 99%
“…The smooth muscle A7r5 cell line was obtained from the thoracic aorta of BDIX rat ( Rattus novergicus) [ 9 ]. The A7r5 cells were purchased from ATCC (CRL-1444) and were expanded in DMEM supplemented with 2 mM glutamine and 10% FBS as described [ 10 , 11 ]. Prior to experiments, culture media was replaced with DMEM 2 mM glutamine and 2% FBS and cells were cultured for further 24 h. Total serum deprivation induced autophagy ( S1 Fig ).…”
Section: Methodsmentioning
confidence: 99%
“…Proliferation of VSMC was determined using MTT assay [ 12 ] and [ 3 H]-thymidine incorporation [ 11 ]. A7r5 migration was evaluated by the wound healing and transwell assays in the presence of bromodeoxiuridine to inhibit cell proliferation [ 11 ].…”
Section: Methodsmentioning
confidence: 99%